Identification of Disease-Associated Variants by Targeted Gene Panel Resequencing in Parkinson's Disease - Daida, Kensuke; Funayama, Manabu; Li, Yuanzhe; Yoshino, Hiroyo; Hayashida, Arisa; Ikeda, Aya; Ogaki, Kotaro; Nishioka, Kenya; Hattori, Nobutaka (Frontiers in Neurology, 2020)
Background: Recent advanced technologies, such as high-throughput sequencing, have enabled the identification of a broad spectrum of variants. Using targeted-gene-panel resequencing for Parkinson’s disease (PD)-associated genes, we have occasionally found several single-nucleotide variants (SNVs), which are thought to be disease-associated, in PD patients. To confirm the significance of these potentially disease-associated variants, we performed genome association analyses, using next-generation target resequencing, to evaluate the associations between the identified SNVs and PD. Methods: We obtained genomic DNA from 766 patients, who were clinically diagnosed with PD, and 336 healthy controls, all of Japanese origin. All data were analyzed using Ion AmpliSeq panel sequences, with 29 PD- or dementia-associated genes in a single panel. We excluded any variants that did not comply with the Hardy–Weinberg equilibrium in the control group. Variant frequencies in the PD and control groups were compared using PLINK. The identified variants were confirmed to a frequency difference of P < 0.05, after applying the Benjamini–Hochberg procedure using Fisher’s exact test. The pathogenicity and prevalence of each variant were estimated based on a public gene database. Results: We identified three rare variants that were significantly associated with PD: rs201012663/rs150500694 in SYNJ1 and rs372754391 in DJ-1, which are intronic variants, and rs7412 in ApoE, which is an exonic variant. The variants in SYNJ1 and ApoE were frequently identified in the control group, and rs201012663/rs150500694 in SYNJ1 may play a protective role against PD. The DJ-1 variant was frequently identified in the PD group, with a high odds ratio of 2.2. Conclusion: The detected variants may represent genetic modifiers or disease-related variants in PD. Targeted-gene-panel resequencing may represent a useful method for detecting disease-causing variants and genetic association studies in PD.